Konsep Supervisi Pendidikan - Fatimah, Metty; Hartanto, Rudy; Priyanto, Catur (TSAQOFAH, 2026)
Educational supervision is a process of providing professional assistance to teachers aimed at continuously improving the quality of instruction and education, with an emphasis on guidance, constructive coaching, and the development of teacher competencies through needs analysis and performance reflection, rather than judgmental practices. This article comprehensively discusses the concept of educational supervision, including its nature, objectives, principles, functions, scope, techniques, and models, as well as the roles and qualifications required of a supervisor. Educational supervision is directed toward improving the quality of teaching and learning processes and outcomes, developing teacher professionalism, refining instructional strategies and assessment, and creating a conducive and innovative learning environment. Effective supervision is grounded in principles such as democratic, cooperative, objective, scientific, adaptive, and continuous approaches. The scope of supervision includes lesson planning, implementation, and evaluation, classroom management, the use of media and technology, and the continuous professional development of teachers. Various supervisory techniques, both individual and group-based, along with supervision models such as clinical, academic, administrative, and collaborative supervision, are employed to support the effectiveness of supervisory practice. The outcomes of supervision are expected to enhance teachers’ pedagogical and professional competence, improve the school climate, and provide a strong foundation for planning comprehensive educational quality improvement.